Upaya Peningkatan Skill Perangkat Desa dan Guru terhadap Pengoperasian Administrasi dengan Microsoft Office di Desa Sumengko, Mojokerto - Yesy Diah Rosita (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
The demand to improve the ability in managing an administration by utilizing Microsoft Office is getting higher. However, there are obstacles that affect the ability of administrative management, such as the age and educational background of the administration manager. The Sumengko Village Government supports the Minister of Home Affairs Regulation No. 47 of 2016 concerning Village Administration and in collaboration with Majaphit Islamic University to facilitate Microsoft Office operation training activities at Sumengko Village Hall. This activity lasted for 4 days consisting of a pre-test, the delivery of theory and the practice of operating Microsoft Office, and post test. The existence of pre-test and post-test activities to find out how much the skill (ability) of the participants has increased towards this training. While the material provided consisted of Microsoft Word, Microsoft Excel and Microsoft Powerpoint. The increase in the ability of participants is classified based on age, recent education, and the position of participants. The age category is divided into 3 parts, namely: age 20-29 years, age 30-39 years, and age 40-49 years. Unlike the case with the last education category is divided into 2 parts, namely high school and graduate level. While the position category consists of village officials and educators. The average magnitude of capacity improvement based on age category, recent education and position for Ms.'s operation. Word, Ms. Excel, and Ms. Powerpoint reached 51.66%, 46.59% and 45.00%.